2021
DOI: 10.3390/ijms22083977
|View full text |Cite
|
Sign up to set email alerts
|

Where and Why Modeling Amyotrophic Lateral Sclerosis

Abstract: Over the years, researchers have leveraged a host of different in vivo models in order to dissect amyotrophic lateral sclerosis (ALS), a neurodegenerative/neuroinflammatory disease that is heterogeneous in its clinical presentation and is multigenic, multifactorial and non-cell autonomous. These models include both vertebrates and invertebrates such as yeast, worms, flies, zebrafish, mice, rats, guinea pigs, dogs and, more recently, non-human primates. Despite their obvious differences and peculiarities, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 266 publications
0
44
0
Order By: Relevance
“…Up to now, the molecular pathways leading to ALS pathophysiology are almost unclear. Therefore, the effort has been made to develop different types of animal models that recapitulate the diverse forms of ALS [ 7 ]. In this regard, both transgenic mice and rats, that express the human SOD1 gene carrying the mutation SOD1 G93A , recapitulate the feature of ALS1 [ 23 ], offering a tool to explore the development of therapeutic strategies for the cure of the disease, and are an appropriate source of ALS1-cells that could be explored for elucidating the pathological molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, the molecular pathways leading to ALS pathophysiology are almost unclear. Therefore, the effort has been made to develop different types of animal models that recapitulate the diverse forms of ALS [ 7 ]. In this regard, both transgenic mice and rats, that express the human SOD1 gene carrying the mutation SOD1 G93A , recapitulate the feature of ALS1 [ 23 ], offering a tool to explore the development of therapeutic strategies for the cure of the disease, and are an appropriate source of ALS1-cells that could be explored for elucidating the pathological molecular pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, whether these dysregulations are a direct causative event of the ALS pathophysiology (e.g., accumulation of undegraded misfolded SOD1 aggregates), or are secondary effects of the progression of the disease, are yet an open question. Therefore, during the last years, the effort has been made on elucidating ALS molecular pathways, also taking advantage of different types of animal models and cell culture models for the different types of the disease [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…RNA-binding protein ATXN2 was first discovered in Saccharomyces cerevisiae as a modifier and interactor of TAR-DNA binding protein 43 (TDP-43) and a CAG trinucleotide expansion in this gene causes it to be a risk factor for ALS. Moreover, it was figured out that GGGGCC repeat expansions in C9orf72 are associated with nucleocytoplasmic transport dysfunction and neurotoxicity ( 55 , 56 ). It is also reported that superoxide dismutase (SOD-1) mutation in yeast leads to protein instability, metabolic regulation perturbance, and cell senescence ( 57 ).…”
Section: Als In Vivo Modeling Platformsmentioning
confidence: 99%
“…Following the initial discovery of mutations in fALS patients, it was possible to model the human disease in living organisms to elucidate the mechanisms underlying MN death. Even though the obvious limitations of animal models, and possibly for this very reason, their number is still growing in the attempt to obtain further items to identify adequate targets for the development of effective therapies, which this very complex disease urgently needs [72][73][74][75].…”
Section: Modelling Human Als In Living Organismsmentioning
confidence: 99%